Pseudo-Effectiveness in Regional Labor Policy: Evaluating Bureaucratic Dynamics of Job Placement Program Implementation in Klaten - Punto Bilowo; Rutiana Dwi Wahyunengseh; Rina Herlina Haryanti (Universitas Pahlawan Tuanku Tambusai, 2026)
This study evaluates the effectiveness of regional labor policy by identifying the bureaucratic factors that influence the implementation of the Job Placement Program (PTK) at the Department of Industry and Labor of Klaten Regency. In practice, however, the program has struggled to achieve its strategic goals of reducing poverty and unemployment, as high levels of administrative activity have not translated into actual job placements for program participants. Employing a case study design with a single embedded unit of analysis, the research investigates the bureaucratic